Performance, emissions, and combustion characteristics of methane-diesel dual-fuel engines: A review - Tripathi, Gaurav; Dhar, Atul (Frontiers in Thermal Engineering, 2022)
Methane is a popular alternative fuel for internal combustion engines due to its availability in many forms such as methane hydrates, natural gas, biogas, compressed natural gas, liquid natural gas, synthetic natural gas, and pipe natural gas. Methane can be effectively used in existing diesel engines in dual-fuel mode with few modifications. Dual-fuel technology helps bridge existing conventional fuel and alternative gaseous fuel-powered conventional engines. The properties of methane, including its higher calorific value, abundant diffusion, and wider flammability limit make it a suitable fuel for improving the performance of compression ignition engine in dual-fuel mode. Methane-diesel dual-fuel engines are an effective technology for reducing vehicle pollution and partially replacing conventional fuels for transport applications. Therefore, a comprehensive review is needed to document the various pathways for the utilization of methane in dual-fuel engines. This study critically compared the combustion, noise, performance, and emission characteristics of various methane-fueled engines to identify the current challenges and future perspectives for the synergistic use of methane to reduce emissions from internal combustion engines.